2018
DOI: 10.1371/journal.pone.0191654
|View full text |Cite
|
Sign up to set email alerts
|

Not explicit but implicit memory is influenced by individual perception style

Abstract: Not only explicit but also implicit memory has considerable influence on our daily life. However, it is still unclear whether explicit and implicit memories are sensitive to individual differences. Here, we investigated how individual perception style (global or local) correlates with implicit and explicit memory. As a result, we found that not explicit but implicit memory was affected by the perception style: local perception style people more greatly used implicit memory than global perception style people. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…How and why some memories are retained better than others is also key in understanding the affective impact of data visualization. As explained by one study [4], "explicit memory refers to the memory that involves conscious recollection of information; on the other hand, implicit memory does not depend on conscious recollection." Furthermore, this study examined how two perception styles affected this: global and local.…”
Section: Literature Reviewmentioning
confidence: 99%
“…How and why some memories are retained better than others is also key in understanding the affective impact of data visualization. As explained by one study [4], "explicit memory refers to the memory that involves conscious recollection of information; on the other hand, implicit memory does not depend on conscious recollection." Furthermore, this study examined how two perception styles affected this: global and local.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These priming tasks provide the opportunity to evaluate the effect of local precedence for the ASD group or global precedence for typically developing participants on memory under conditions that favor automatic processing uncontaminated by conscious attentional processes as well as promoting a participant's preferred perceptual processing style. Recently, Hine and Tsushima (2018) shown that not explicit but implicit memory was affected by the perception style (perceptual index calculated to the Navon task): local perception style people more greatly used implicit memory than global perception style people.…”
Section: Introductionmentioning
confidence: 99%